ANALISIS PENGARUH IKLIM ORGANISASI DAN MOTIVASI TERHADAP KOMITMEN KERJA KARYAWAN DI PERUSAHAAN MATARAM SAKTI MUARA BULIAN - ETTY SISWATI (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
This study aims to determine the influence analysis of organizational climate and motivation to work commitment of employees at PT Mataram Way Muara Bulian in this study used primary data , data collection techniques by spreading questionnaires to employees at PT Mataram Way Bulian Estuary. The analysis used in this study are in diskritif qualitative and SPSS software . The results obtained by using multiple linear regression hypothesis . By using two hypotheses testing are partial test and test simultaneously . The results show that the partial effect that the influence of Organizational Climate on the commitment of employees at PT Mataram Way Bulian Estuary . Similarly, the results of variable organizational and Motivation on Commitment.